The Implementation of Jigsaw Technique to Overcome Learning Loss on Post Pandemic Situation in Learning Narrative Text at Senior High School - Rifda Zuliyarti; Muhammad Andriana Gaffar (STKIP Yapis Dompu, 2023)
This research aims to overcome learning loss in high school students in a post-pandemic situation by applying the jigsaw technique in teaching narrative texts. This research was conducted at Mekar Arum High School in class 10 MIPA 1 with 28 participants. This research uses a qualitative method with a Classroom Action research approach. Data collection techniques in this research used three instruments: observation, interviews, and the field. Based on the results of research conducted by researchers, it can be concluded that the application of the jigsaw technique carried out by the teacher runs smoothly. According to the procedure, then in the application of the jigsaw technique students can follow the teacher's directions well, students have also participated in the discussion process with maximum mutual cooperation and maximally fulfilling the responsibilities requested by the teacher, the interaction of students with their group mates has also started to be well established as well as interactions with the teacher, students have also been able to show the results of their discussions with confidence and when the teacher asks some questions all students can answer questions from teachers quickly, responsively, and correctly. Then, some of the consequences of learning loss that occur in students by applying the jigsaw technique in learning narrative text can overcome the problems of learning loss that occur in students.